Extra-curricular activitities of grade ten students and factors associated in Sinhala medium schools of Matale Municipal Council area. - Weerasinghe, I. E (My University, 2006)
This cross-sectional study was carried out to determine the extent of participation in extracurricular activities and factors associated in grade ten school children in Matale Municipality Area (MMA). Six hundred and twenty (620) students of Government Sinhala Medium schools in the MMA participated in the study. The selection of the sample was done using cluster sampling. The study instruments included a self-administered questionnaire, data extraction sheet and a focus group discussion guide. The availability and types of extra-curricular activities in schools differed according to type of schools. In the study population, 65.3 percent participated in ECA. Those who participated were involved in sports( 46.9 percent), aesthetics (11.1 percent), clubs and associations (18.5 percent) and leadership activities (29.8 percent). This study shows that a variety of ECA are carried out in schools and the number of ECA as well as the types of ECA differ according to the type of school .ECA participation in Grade 10 students is affected by many factors. Male sex and siblings' participation in ECA increase the ECA participation and that there is no association between ECA participation and academic performance. Yet, ECA participation by sex is significantly associated with academic performance. It also highlights the importance of improving school facilities to enhance extra-curricular activity participation in school adolescents.